Same dish with new ingredients? —Implicit conceptions of first-year pre-service teachers about the role of emotions in learning processes - Bächler, Rodolfo; Quiroz, Byron; Segovia-Lagos, Pablo; Otárola, Macarena; Cofré, Fernando (Frontiers in Psychology, 2025)
In the context of the emotional turn experienced in the world and in educational systems, this study undertook the task of examining the conceptions that pre-service teachers of first year have re-garding the role of emotions in educational processes. For this purpose, a dilemma questionnaire was applied to a sample of 72 first-year pre-service teachers from Chilean universities. The in-strument considered three types of conceptions called, in an increasing order of complexity, “behavioral reductionism,” “influence of emotions on cognition” and “cognitive emotional in-tegration.” The results show a rejection of the simplest and the most complex conception, and a large degree of adherence to the conception that separates emotions from cognitive processes, called “influence of emotions on education.” There are analyzed the differences found according to the gender of the students and a reflection on the possibility that the adherence to dualistic con-ceptions could be a way of reacting to an education based on fear as the only driving force for learning.